PENANAMAN KARAKTER DISIPLIN OLEH GURU IPS SELAMA PEMBELAJARAN DARING PADA PESERTA DIDIK KELAS VIIIB - Yudha Dwi Hardiyanto; Yohanes Bahari; Achmadi Achmadi (Universitas Tanjungpura, 2022)
Abstract This study aims to obtain a picture of instilling discipline in class VIII B students of SMPN 11 Pontianak during online learning. This study focuses on determining efforts made by social studies teachers to instill discipline in students during online learning. The method used is qualitative research with a descriptive approach. Data were analyzed using data reduction, data display, and drawing conclusions and verification, and tested for validity using data triangulation and theoretical triangulation techniques. Based on the results, students‟ discipline is determined by two factors, namely internal and external factors. Internal factors include fear of being bullied, laziness, habits, and difficulty understanding the learning materials. Meanwhile, external factors include the role of parents, teachers, and schools. Efforts made by the teachers in instilling discipline in students include being good examples and role models for students, providing motivation and positive reinforcement for them, and providing sanctions to students who violate the code of conduct. Keywords: character building, discipline, students, online learning